Answer:
Step-by-step explanation:
<h3>The rate of change between (-3,6) (0,-3) is -3</h3>
<em><u>Solution:</u></em>
Given that,
We have to find the rate of change between (-3,6) (0,-3)
<em><u>The rate of change is given as:</u></em>
![Rate\ of\ change = \frac{y_2-y_1}{x_2-x_1}](https://tex.z-dn.net/?f=Rate%5C%20of%5C%20change%20%3D%20%5Cfrac%7By_2-y_1%7D%7Bx_2-x_1%7D)
From given,
![(x_1, y_1) = (-3, 6)\\\\(x_2, y_2) = (0, -3)](https://tex.z-dn.net/?f=%28x_1%2C%20y_1%29%20%3D%20%28-3%2C%206%29%5C%5C%5C%5C%28x_2%2C%20y_2%29%20%3D%20%280%2C%20-3%29)
<em><u>Substituting the values we get,</u></em>
![Rate\ of\ change = \frac{-3-6}{0+3}\\\\Rate\ of\ change = \frac{-9}{3}\\\\Rate\ of\ change = -3](https://tex.z-dn.net/?f=Rate%5C%20of%5C%20change%20%3D%20%5Cfrac%7B-3-6%7D%7B0%2B3%7D%5C%5C%5C%5CRate%5C%20of%5C%20change%20%3D%20%5Cfrac%7B-9%7D%7B3%7D%5C%5C%5C%5CRate%5C%20of%5C%20change%20%3D%20-3)
Thus rate of change is -3
Aaaaaaaaaaaaaasssssssssssssssuiiiiiiiiiiiiiyyyyyyyyyyyyyyaaaaaaaaaaaaxrgcghgg%%%%%%%